2012
DOI: 10.3892/mco.2012.54
|View full text |Cite
|
Sign up to set email alerts
|

L-type amino acid transporter 1 expression is highly correlated with Gleason score in prostate cancer

Abstract: Abstract. Upregulation of L-type amino acid transporter 1 (LAT1), a member of the system L amino acid transporter family, may be detected by immunohistochemical methods. Immunoreactive LAT1 expression in prostate cancer is considered to be a promising biomarker for high-grade malignancy. However, the mutual association between LAT1 and Gleason score, the most fixed indicator for grading the malignancy of prostate cancers, remains to be elucidated. The aim of this study was to clarify the correlations between L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 25 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…The expression of LAT1 mRNA is restricted to certain organs, such as the brain, spleen, placenta, and testis (3)(4)(5). Furthermore, it has been reported that LAT1 is highly expressed in cancer tissue of various types of cancer, including oral squamous cell carcinoma (6), esophageal carcinoma (7), gastric cancer (8), prostate cancer (9), non-small cell lung carcinoma (10), biliary tract cancer (11), pancreatic cancer (12), and breast cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of LAT1 mRNA is restricted to certain organs, such as the brain, spleen, placenta, and testis (3)(4)(5). Furthermore, it has been reported that LAT1 is highly expressed in cancer tissue of various types of cancer, including oral squamous cell carcinoma (6), esophageal carcinoma (7), gastric cancer (8), prostate cancer (9), non-small cell lung carcinoma (10), biliary tract cancer (11), pancreatic cancer (12), and breast cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…18 F]fluciclovine detected PCa lesions including primary PCa [17], local recurrence after radical prostatectomy [15], and metastasis in pelvic lymph nodes and bone [15,18,19] -dependent system ASC transporters (especially ASCT2), and Na + -independent system L transporters (especially LAT1), which are upregulated in various cancers including PCa [20][21][22] and are thought to be involved in fluciclovine uptake into prostate cancer cells [23,24]. Moreover, the affinity of fluciclovine for human ASCT2 is similar to that of natural neutral amino acids such as L-alanine and L-serine [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several amino acid transporter systems are over expressed in prostate cancer; specifically large neutral amino acid transporters (system L: LAT1, LAT3, and LAT4) and alanine-serine-cysteine transporters (system ASC: ASCT1 and ASCT2) (5,6). Of these, LAT3, ASCT1, and ASCT2 are upregulated with androgen simulation and LAT1 and ASCT2 are associated with a more aggressive tumor phenotype (7). Anti-1-amino-3-[ 18 F]-flurocyclobutane-1-carboxylic acid (18F-fluciclovine) is a non-naturally occurring amino acid first synthesized by Dr. Mark Goodman, and initially developed for the evaluation of cerebral gliomas (8).…”
Section: Introductionmentioning
confidence: 99%